Comment on "Investigating Earth's Formation History Through Copper & Sulfur Metal–Silicate Partitioning During Core‐Mantle Differentiation" by Mahan et al. Issue 12 (6th December 2019) - Jennings, Eleanor S.; Wade, Jon; Llovet, Xavier
Key Points: EPMA analyses of small areas are prone to analytical artifacts such as fluorescence that can be problematic when measuring minor elements In the study of Mahan et al. (2018), fluoresced Cu X‐rays from the Cu sample holder account for ~70% of their measured Cu concentrations We quantified the contribution of spurious Cu X‐rays to the primary signal using Monte Carlo particle transport simulations Abstract: The physical and chemical conditions of terrestrial core formation play a key role in the distribution of elements between the Earth's silicate mantle and metallic core. To explore this, Mahan, Siebert, Blanchard, Badro, et al. (2018, https://doi.org/10.1029/2018JB015991 ) present experimentally‐derived partitioning data, showing how Cu distributes itself between metal and silicate at lower‐mantle PT conditions with implications for planetary accretion and core formation. Eight experiments were performed in a diamond anvil cell, and each sample was welded to a copper grid for analysis. An offset in partitioning behavior was subsequently noted between the high‐ P experiments and the lower‐ P data set. However, when analyzing the diamond anvil cell experiments by electron probe microanalysis, the authors did not account for the secondary fluorescence of Cu that arises from the sample holder. Using Monte Carlo simulations of X‐ray and electron transport, we show that the fluorescence of the Cu grid, originating from high‐energy continuum X‐rays emitted from the sample, makes a significant contribution to the reported measurement of Cu in both the silicate and metallic phases. This is in good agreement with previous measurements made on Cu‐free analogs. On average, around 70% of the published Cu concentrations are attributable to X‐rays that originate externally to the sample. The reported offset in K D met‐sil at high pressures may reflect the different experimental and analytical protocol used, rather than a true pressure effect. Although adequate post hoc corrections can be made, uncertainties around the exact sample and detector geometries make it difficult to refine simulations and derive accurate correction factors for each experiment.